2022
DOI: 10.3390/su14042273
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effects of Heavy Metals in Soils after Removal by Nanoscale Zero-Valent Iron with Three Methods

Abstract: Nanoscale zero-valent iron (nZVI) has been broadly applied in the remediation of heavy metals pollution. In this research, the toxicity characteristic leaching procedure (TCLP), the in vitro gastrointestinal (IVG) method, and the diffusive gradients in thin-films (DGT) technique were used to evaluate the effects of heavy metals in soil with remediation by nZVI. The results indicate that, compared with the dose of 0.5 g·L−1, the nZVI in the dose of 1.0 g·L−1 can remove the heavy metals in the soil. The leaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The DGT technique has been used to assess the PTE mobility variations in soil remediation processes in 24 recent papers examined in this review. Among the studied topics, the effects on PTE mobility in soils were tested after the addition of organic amendments (Grüter et al 2019 ; Luo et al 2021 ; Mohseni et al 2021 ; Sun et al 2022 ; Zhao et al 2022 ), biochar (Bidar et al 2019 ; Babalola and Zhang 2021 ; Gao et al 2022a , b ), and inorganic amendments and sludge (Neu et al 2018 ; Xu et al 2019b ; Manzano et al 2019 ; Zhang et al 2019 ; Mohseni et al 2021 ; Senila et al 2022 ; Zhang et al 2022a ; Zhang et al 2022b ). Other authors used DGT to assess the effect of soil moisture in PTE mobility (Li et al 2015 ; Wang et al 2020 ; Zhao et al 2021 ; Wang et al 2022b ) or to evaluate the effect of hyperaccumulator plants in PTE mobilization in rhizosphere (Senila et al 2013 ; Li et al 2016 ; Zheng et al 2019 ).…”
Section: Dgt Applications For Heavy Metal Labile Fractions In Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…The DGT technique has been used to assess the PTE mobility variations in soil remediation processes in 24 recent papers examined in this review. Among the studied topics, the effects on PTE mobility in soils were tested after the addition of organic amendments (Grüter et al 2019 ; Luo et al 2021 ; Mohseni et al 2021 ; Sun et al 2022 ; Zhao et al 2022 ), biochar (Bidar et al 2019 ; Babalola and Zhang 2021 ; Gao et al 2022a , b ), and inorganic amendments and sludge (Neu et al 2018 ; Xu et al 2019b ; Manzano et al 2019 ; Zhang et al 2019 ; Mohseni et al 2021 ; Senila et al 2022 ; Zhang et al 2022a ; Zhang et al 2022b ). Other authors used DGT to assess the effect of soil moisture in PTE mobility (Li et al 2015 ; Wang et al 2020 ; Zhao et al 2021 ; Wang et al 2022b ) or to evaluate the effect of hyperaccumulator plants in PTE mobilization in rhizosphere (Senila et al 2013 ; Li et al 2016 ; Zheng et al 2019 ).…”
Section: Dgt Applications For Heavy Metal Labile Fractions In Soilmentioning
confidence: 99%
“…The process was investigated using mesocosm coupled with DGT for in situ visualization. Zhang et al ( 2022b ) used the DGT to assess the effects of soil remediation by nanoscale zero-valent iron on heavy metal (Cr, Cu, Zn, Pb) bioavailability in soil.…”
Section: Dgt Applications For Heavy Metal Labile Fractions In Soilmentioning
confidence: 99%
“…According to the "Solid Waste Leaching Toxicity Leaching Method -Horizontal Oscillation Method" (HJ 557-2010) [44], leaching measurements were carried out on sieved and dried recycled aggregate samples and the treated products. Table 4 shows the contents of phosphorus, fluorine, and some heavy metals in the leachate of raw PG and different recycled aggregate samples after toxic leaching.…”
Section: Environmental Impactmentioning
confidence: 99%
“…For example, sewage sludge biochar tubule can significantly decrease the total Cr and Pb content in contaminated soil by adsorption, ion exchange, complexation, and precipitation, which was concluded from a characteristic analysis [37]. Nanoscale zero-valent iron (nZVI) and modified nZVIs can reduce Cr (VI) to Cr (III) in contaminated soils, which in turn generates Cr(OH) 3 precipitate, thereby reducing its bioavailability and plant bioaccumulation [38,39]. It has also been found that the use of some soil conditioners may cause some damage to the nutrients, structure, and microbial community of the soil [40]; add additional costs; and affect whether they can be used all year.…”
Section: Introductionmentioning
confidence: 99%